Clinical Study of the Manifestations of Diabetes Mellitus in Oral Cavity: Clinical Study of the Manifestations of Diabetes Mellitus - Khalid, Basil; Khan, Muhammad Athar; Hameed, Marij; Nazir, Samar; Haider, Ehsan; Nazir, Ammara (Pakistan Journal of Health Sciences, 2024)
Diabetes Mellitus, a chronic illness affecting all ages, contributes to worldwide mortality and morbidity. Oral consequences of diabetes are less well-documented than microvascular and macrovascular issues. It's been called a growing endemic disease. About 285 million people worldwide have diabetes. Objectives: To enhance the understandings of oral signs and the complications associated particularly with Diabetes Mellitus. Methods: Patients aged 40 to 75 were included in the study without gender discrimination All patients were known diabetic (NIDDM) and having the disease from at least last 7 years. clinical values and labs (RBS and HbA1C were taken to assess the control level of the disease) were taken from their record files. Results: Family history of non-idiopathic diabetic retinopathy (NIDDM) was found in (59.44%) of the population. NIDDM caused oral lesions in close to (79.34%) of individuals. 13 patients presented with white lesions. Buccal mucosa remained the most common site of involvement, with desquamative gingival involvement in 3 patients. Oral Lichen Planus was seen in 13 patients (2.53%). Halitosis in 309 patients (60.23%), Mild xerostomia in 184 patients (35.87%), tooth mobility>2mm was found in 106 patients (20.66%), Angular Cheilitis seen in 51 patients (9.94%), and oral ulcers / RAS were reported in 117 patients (22.81%). Conclusions: NIDDM can cause oral mucosal pathologies. Routine dental screenings and early detection of these alterations may improve oral health, medication adherence, and problems in afflicted persons.